The application of the principle of wave superposition in ultrasonic measurement of lubricant film thickness. (April 2019) - Dou, Pan; Wu, Tonghai; Luo, Zhaopeng; Peng, Zhongxiao; Sarkodie-Gyan, Thompson
Highlights: The principle of wave superposition is applied to analyse resonant model. The phase difference π is the essential resonance mechanism. The minimum and zero-crossing methods are highly consistent in a wide range. The influence of the number of echoes on the resonant model has been verified. The influence of the solid layers on the resonant model has been determined. Abstract: The principle of resonance is often applied in the ultrasonic measurement of the thickness of lubricant films. The information data relating to the thickness of the lubricant film involves the acquisition of the resonance frequency of a continuous wave with the application of a continuum model. However, ultrasonic signals are often times, generated by piezoelectric elements but these exhibit some variations from the continuous wave because they are dispersed pulses that have a wide range of frequency bandwidths. In this paper, the authors have applied the principle of wave superposition for the measurement of lubricant film thickness. This principle exhibits the capability to generate the resonant mechanisms of the pulse waves. The implemented theoretical analysis in this research work, depicted that the principle of wave superposition may demonstrate more applicability than the continuum model under the condition of the partial inclusion of the reflected pulse waves. The application of this principle facilitated the analysis of the resonant mechanisms of the pulse wave from the phase variations of the reflected echoes. It followed the further investigations into the influence of both the number of the reflected echoes and the materials of the solid layers on the film resonance method. The results of these investigations were validated using experimental results.